'Ob-La-Di Ob-La-Da' Paul McCartney, Diaspora and the Politics of Identity - Stratton, Jon (IASPM Australia/New Zealand, Dunedin, 2013)
'Ob-La-Di Ob-La-Da' is commonly considered to be one of the Beatles more trite songs. A slice of happy-go-lucky pop-ska, it was recorded in June 1968 during the sessions for the eponymously titled double album, usually known as the White Album, released in November of that same year. The lyrics describe the lives of Desmond and Molly, focusing on their marriage and their happy-ever-after existence. The song is a romance. However, the chorus of 'Ob la di ob la da life goes on' suggests the very mundanity of their life. It is theirs alone, but what makes it special, their love, could be anybody's. 'Ob-La-Di Ob-La-Da' was, as all the Beatles knew, the most commercial track on the album but, as Ian MacDonald writes in Revolution in the Head, his track by track account of the Beatles' recordings: 'Fed up with it, the others vetoed it as a single and Marmalade cashed in, taking it to No 1' (2008, p.295). As we shall see, it was not as simple as this. While Marmalade's version was, indeed, the most successful, the Bedrocks, a group from Leeds composed of Caribbean migrants, climbed as high as number 20 in the UK singles chart with a reading of the song that was simultaneously rockier and more Jamaican. That same year Joyce Bond, who divided her time between Jamaica and London, recorded a version that had a more pronounced ska rhythm and the following year the Heptones, one of the most significant Jamaican rock-steady groups, released their version.